Analisis Motivasi Belajar Peserta Didik SD Negeri Ngaliyan 01 - Habib Ali (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2023)
The quality of good human resources can be emphasized through education. Through education, a person has the opportunity to change himself to become a better individual, from initially not understanding to understanding. A person can be said to be successful in his education if he is able to show changes in thinking abilities, attitudes and skills. The results of this study explained that as many as 15 students (65%) had sufficient learning motivation, and 8 students (35%) had high learning motivation. The purpose of this study is to find out how to analyze the learning motivation of SD Negeri Ngalaiyan 01 students. The research method used is qualitative research method and the data collection uses a questionnaire and observation. This research is expected to be useful for researchers and readers as a source of literature. Keywords: education, motivation, learning